If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3(1 + -1x) = -2x + -1(1 + -1x) 4x + (1 * -3 + -1x * -3) = -2x + -1(1 + -1x) 4x + (-3 + 3x) = -2x + -1(1 + -1x) Reorder the terms: -3 + 4x + 3x = -2x + -1(1 + -1x) Combine like terms: 4x + 3x = 7x -3 + 7x = -2x + -1(1 + -1x) -3 + 7x = -2x + (1 * -1 + -1x * -1) -3 + 7x = -2x + (-1 + 1x) Reorder the terms: -3 + 7x = -1 + -2x + 1x Combine like terms: -2x + 1x = -1x -3 + 7x = -1 + -1x Solving -3 + 7x = -1 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -3 + 7x + x = -1 + -1x + x Combine like terms: 7x + x = 8x -3 + 8x = -1 + -1x + x Combine like terms: -1x + x = 0 -3 + 8x = -1 + 0 -3 + 8x = -1 Add '3' to each side of the equation. -3 + 3 + 8x = -1 + 3 Combine like terms: -3 + 3 = 0 0 + 8x = -1 + 3 8x = -1 + 3 Combine like terms: -1 + 3 = 2 8x = 2 Divide each side by '8'. x = 0.25 Simplifying x = 0.25
| 490-56=434 | | 1x+3(1-x)=3x+0(1-x) | | 3x+2y=165 | | 5x+-4(1-x)=1x+0(1-x) | | J=p(B-x) | | -3x+-2(1-x)=-5x+4(1-x) | | 32(31-5.5x)=11(5x-10)+39.4 | | 0=3+(x+6)+8x | | 40000=3100x+2500 | | 0x+0(1-x)=4x+-1(1-x) | | -16t^2+142t+384=0 | | -1x+-1(1-x)=-4x+4(1-x) | | 2x+3y=160 | | -16t^2+142t+64=0 | | 90=n(2n+3) | | 286=8x+20 | | 60+60+(X-20)=180 | | x^3-13x^2-128x+1020=y | | z+(-7z)+z+z= | | -2x+1(1-x)=-1x+-5(1-x) | | 2(x-5)-7=3 | | 286=8x+2500 | | -2x+1(1-x)=-1x+5(1-x) | | 35+4x=-X-5 | | 3/4x-8/4=1/4x-4 | | 0=t+3+8(5+t) | | y=x^3-13x^2-128x+1020 | | 5x^-1/5(4x^5-x^1/5) | | 180x=1665 | | 12x^3+4x^2+1x=0 | | 2x+-5(1-x)=-1x+-3(1-x) | | .07x=48.93 |